The average position of the first maximum in a sample of geometric random variables - Margaret Archibald; Arnold Knopfmacher (Discrete Mathematics & Theoretical Computer Science, 2007)
We consider samples of n geometric random variables $(Γ _1, Γ _2, … Γ _n)$ where $\mathbb{P}\{Γ _j=i\}=pq^{i-1}$, for $1≤j ≤n$, with $p+q=1$. The parameter we study is the position of the first occurrence of the maximum value in a such a sample. We derive a probability generating function for this position with which we compute the first two (factorial) moments. The asymptotic technique known as Rice's method then yields the main terms as well as the Fourier expansions of the fluctuating functions arising in the expected value and the variance.